PERAN DINAS SOSIAL KOTA PEKANBARU DALAM REHABILITASI GELANDANG DAN PENGEMIS DI KOTA PEKANBARU TAHUN 2022 - Adha, Alfandy; Harirah, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia is a developing country where the problem of poverty, including homelessness and beggars, is still widespread in urban areas. This phenomenon also occurs and is part of the life of big cities such as Pekanbaru City, this is due to the increase in population which is not balanced with adequate employment opportunities, and unequal employment opportunities. The aim of this research is to determine the role and obstacles of the Pekanbaru City social service in carrying out social rehabilitation for homeless people and beggars in Pekanbaru City. The approach used in this research uses qualitative research with the type of research being descriptive, the data needed is primary data and secondary data so that data collection is carried out by interviews and documentation, data analysis techniques are by data reduction, data presentation, drawing conclusions. The research results show that the role of the Pekanbaru City social service in carrying out social rehabilitation for homeless people and beggars is that the Social Service has carried out its role in carrying out the rehabilitation of homeless people and beggars in accordance with Perwako No. 97 Tahuin 2016 even though it is only implementing basic rehabilitation. The obstacles experienced by the Pekanbaru City Social Service in carrying out social rehabilitation for homeless people and beggars consist of a minimal budget, inadequate existing facilities, and the mentality of homeless people and beggars. Keywords : Social Rehabilitation, Homelessness, Beggars, Social Services.